CLINICAL FEATURES OF HEART FAILURE IN PATIENTS WITH ISCHEMIC HEART DISEASE AND THYROTOXICOSIS - Khusainova Munira Alisherovna; Yarmatov Suvon Totlibayevich; Gafforov Xudoyor Xudoyberdiyevich; Kamolova Diyora Jamshedovna (Journals Park Publishing, 2022)
Chronic heart failure is a clinical syndrome in some diseases, accompanied by characteristic symptoms (shortness of breath, decreased physical activity, fatigue, edema, etc.) associated with inadequate perfusion of organs and tissues at rest or during exercise, accompanied by fluid retention in the body and its accumulation in soft tissues. The main causes of CHF include: arterial hypertension (95.5%), coronary heart disease (69.7%), myocardial infarction (15.3%), diabetes mellitus (15.9%). The combination of coronary heart disease and arterial hypertension occurs in most patients with CHF. COPD (chronic obstructive pulmonary disease) accounts for 13% of all causes of CHF, chronic and paroxysmal atrial fibrillation – 12.8%, acute cerebral circulation disorder – 10.3%. Ischemic heart disease is a myocardial lesion caused by a disorder of the coronary circulation, resulting from a violation of the balance between the coronary blood flow and the metabolic needs of the heart muscle. In other words, the myocardium needs more oxygen than it receives from the blood. Coronary heart disease can occur acutely (in the form of myocardial infarction), as well as chronically (periodic attacks of angina pectoris). Тhyrotoxicosis is a syndrome caused by hyperfunction of the thyroid gland, manifested by an increase in the content of hormones: triiodothyronine (T3), thyroxine (T4). Depending on the level of occurrence of the disorder, the following types of hyperthyroidism are distinguished: primary — thyroid gland, secondary — pituitary gland, tertiary — hypothalamus.
Keywords: chronic heart failure, coronary heart disease, thyrotoxicosis, vegetative imbalance